The Influence of Job Satisfaction on Work Motivation of Workers in Coal Mining Companies - Siregar, Indri; Hizkal, Muhammad; Pradana, Risyad Kharisma; Ichsan, Mohammad (Journal of Applied Business Administration, 2024)
This research examines the impact of job satisfaction on employee motivation in coal mining companies. Satisfied employees tend to be more motivated, which in turn can improve company performance. Factors such as recognition for performance, career development, and intrinsic satisfaction with work play an important role in employee motivation. This research aims to provide insight into the relationship between work motivation, employee satisfaction, and operational performance in the mining industry. This research investigates factors that influence employee engagement at work, including career development, pay and benefits, social needs, and work motivation. Using a quantitative approach and survey methods, this research hypothesizes that job satisfaction influences work motivation. By utilizing survey methods with questionnaires and interviews, quantitative data was collected from field workers in the mining sector. Statistical methods are used to analyze data and test the influence between research variables. References include theories of motivation and job satisfaction, as well as related research in the mining industry. This research utilizes a quantitative approach and survey method by distributing questionnaires to 83 field workers at PT AI. The research hypothesizes that job satisfaction influences work motivation. This study employs validity tests, reliability tests, simple linear regression analysis, correlation coefficient, coefficient of determination, and t-tests. The results of this study indicate that there is a significant influence of job satisfaction on work motivation among mining workers at PT AI.